Benford Law and fraudulent financial statements of unlisted enterprises - Nguyễn Thị Thu Hiền; Đặng Anh Tuấn (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kinh tế và Quản trị kinh doanh)
The private sector plays a vital role in the economic growth of a country and contributes significantly to the state’s budget through tax revenue. However, many enterprises still engage in tax evasion and tax avoidance by manipulating financial statements. To address this issue, a study was conducted to determine whether the net profit data of the unlisted enterprises complied with Benford’s Law and whether firms manipulated data to minimize tax liability. The study collected research data on unlisted enterprises in the private sector, excluding foreign direct investment and state-owned enterprises, in 2022. The study showed that most enterprises’ net profit target data complied with Benford’s Law. However, 1,588 firms with negative net profits showed signs of adjusting profits to reduce tax liability. These enterprises had the first digits 1 and 3, the second digits 0, 1, and 3, and the first two digits 20 and 30, which belonged to the opposing net profit target. This finding indicated that Benford’s Law could be used to identify potentially manipulated data.